World Research: Networking, Growth, and Diversification - Marginson, Simon (International Higher Education, 2020)
Since the Internet began in 1990, there has been rapid worldwide growth in research funding and science paper output. Bottom-up global collaboration has expanded rapidly, many lower middle-income countries have their own science systems, and almost one-quarter of all papers have international coauthors. Research agendas are now often shaped in the global network, not national systems. Research power has become more diversified, with China and East Asia, India, Iran, Brazil, and others becoming stronger.